Characterization of hydrogeochemistry of the hot springs on both sides of the Nujiang River near Baoshan in the Yunnan-Tibet Geothermal Belt - Jingru Ma; Xun Zhou; Yanqiu Wu; Linyang Zhuo; Mengmeng Wang; Yu Liu; Hongfei Xu; Yixuan Wang; Guangbin Tao; Jingwen Cui; Chun Wang; Yanxiang Shi; et al. (Journal of Hydrology: Regional Studies)
Study region: The Nujiang Fault Zone near Baoshan in western Yunnan. Study focus: Major hydrochemical elements and stable isotopes of 15 hot spring water samples are analyzed to reveal hydrogeochemical evolution processes, recharge sources, geothermal conditions, and structural control genesis of the hot springs. New hydrological insight for the region: Baoshan is experiencing a wave of clean energy development, specifically geothermal energy. The Nujiang Fault Zone, which separates the Tengchong Block from the Baoshan Block, constitutes a low- to medium-temperature geothermal system characterized by numerous hot springs. The hot springs under investigation are located near Baoshan along the Nujiang Fault. Four hydrochemical types have been identified, with HCO3-Ca⋅Mg being the predominant type. The primary components of spring waters originate from the weathering or dissolution of carbonate and silicate minerals, as well as the reverse cation exchange. Stable isotopes indicate that these hot springs are predominantly formed by the atmospheric precipitation during the summer monsoon. The recharge areas are located in the mountainous regions around the Nujiang River, at elevations ranging from 1606 to 2504 m and temperatures between 3°C and 8°C. The estimated temperature of the geothermal reservoir ranges from 73°C to 192°C. During the ascent process, the mixing ratio of cold water is between 60 % and 79 %, and the circulation depth ranges from 1928 to 4221 m. The positive correlation between Li and Cl indicates that hot springs originate from the same parent geothermal fluid controlled by the Nujiang Fault or by two secondary faults intersecting at depths. The hot springs with shallower circulation depths are mainly composed of HCO3-Ca⋅Mg type, while the deeper circulating spring waters consist primarily of HCO3-Na type. The height difference between the discharge location of the hot springs and the surface of the Nujiang River correlates positively with the geothermal reservoir temperature. This paper emphasizes the hydrogeochemical characterization of hot springs within regional fault zones, which holds significant implications for the development and exploration of geothermal systems in similar structural control areas.